2015
DOI: 10.3892/or.2015.3939
|View full text |Cite
|
Sign up to set email alerts
|

SHP-1 overexpression increases the radioresistance of NPC cells by enhancing DSB repair, increasing S phase arrest and decreasing cell apoptosis

Abstract: Abstract. The present study aimed to investigate the influence of SHP-1 on the radioresistance of the nasopharyngeal carcinoma (NPC) cell line CNE-2 and the relevant underlying mechanisms. The human NPC cell line CNE-2 was transfected with a lentivirus that contained the SHP-1 gene or a nonsense sequence (referred to as LP-H1802Lv201 and LP-NegLv201 cells, respectively). Cells were irradiated with different ionizing radiation (IR) doses. Cell survival, DNA double-strand breaks (DSBs), apoptosis, cell cycle dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Chk2, an important signal transduction protein in the DNA damage pathway, activates a variety of downstream DNA repair genes by phosphorylation. Studies have shown that the increased activation of ATM/Chk2 leads to the enhancement of DNA repair, resulting in radioresistance 58 . Activated ATM can increase the levels of activated p53 protein and the ability for DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Chk2, an important signal transduction protein in the DNA damage pathway, activates a variety of downstream DNA repair genes by phosphorylation. Studies have shown that the increased activation of ATM/Chk2 leads to the enhancement of DNA repair, resulting in radioresistance 58 . Activated ATM can increase the levels of activated p53 protein and the ability for DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation found that SHP-1 was highly expressed in NPC tissues in contrast to normal nasopharyngeal mucosa and was associated with local recurrence and metastasis after radiotherapy in NPC patients (27). Further research showed that SHP-1 overexpression increased the radioresistance of NPC cells by enhancing DSB repair, increasing S phase arrest and decreasing cell apoptosis (34). To assess whether quinalizarin has an influence on SHP-1 expression, we treated NPC cells with quinalizarin and detected the expression of SHP-1.…”
Section: Discussionmentioning
confidence: 97%
“…P53, a transcription factor that can activate the inhibitor of the cell cycle and participate in DNA damage response and transcription of apoptosis [ 43 ], may also play a role in premature aging by causing reactive damage to DNA [ 44 ]. p53 is associated with the two key kinases of ataxia telangiectasia and rad3-related protein-checkpoint kinase 1 pathway [ 45 ] that induce the transcription of cell cycle suppressor p21 gene and delay damaged G1 cells from entering S phase, preventing new start events at the beginning of the duplication process and slowing down the branching processes of reproduction of UV-irradiated cells in the S phase. Thus, p53 transiently suppresses DNA synthesis in UV-damaged cells [ 46 ].…”
Section: Role Of Ros In Uv-induced Photodamage Of the Skinmentioning
confidence: 99%